Development of Electronic Module Based on POE (Prediction, Observation, Explanation) in Natural Organic Chemistry Learning - Alfia Novera Indah Esa Kasih; Agus Sundaryono; Euis Nursa’adah (EduChemia (Jurnal Kimia dan Pendidikan), 2021)
Organic Chemistry of Natural Materials (KOBA) is a course that requires students to define, classify, and isolate compounds of natural materials. However, there are some students who still have difficulty understanding the application of material in everyday life. So that learning materials are needed that can make students active and independent in solving problems related to real life, namely by making E-Modules combined with the POE learning model. This study aims to obtain the validity of E-Module Based on POE products and to obtain questionnaire data on the responses of chemistry education students after using E-Module Based on POE. This type of research is Research and Development (R&D) with the Thiagarajan learning development model which consists of 4D (define, design, develop, and disseminate) which involves one group of subjects. The results showed that the E-Module Based on POE utilizing the Flip PDF Professional application produced a valid E-Module with an average CVR value of one. And the student response questionnaire data to the E-Module developed was 98.04% with the very good category. Means that the E-Module Based on POE developed can be a supplement to KOBA teaching materials.